An examination of energy efficiency retrofit scheme applications by low-income households in Ireland - Arya Pillai; Miguel Tobar Rea\~nos; John A. Curtis (The Economic and Social Research Institute (ESRI), 2021)
This paper studies the determinants of why low-income households in Ireland abandon energy efficiency retrofit applications using administrative data from a targeted energy efficiency grant. By applying for the scheme the applicants overcome any financial barriers for undertaking retrofits and demonstrate their willingness to improve the energy efficiency of their dwellings. Hence this study contributes to the scarce literature on non-financial barriers preventing low-income households from undertaking energy efficiency retrofits. Contrary to previous findings, we find that the higher the number of retrofits to be implemented, the lower the probability of households abandoning their applications. We also find that planning to undertake retrofits such as ventilation, which can significantly improve the health and safety standards of the dwelling, is associated with a higher probability of abandonment. Both findings indicate the presence of key behavioural and informational barriers which prevent low-income households from fully comprehending the purpose or benefits of proposed energy efficient retrofits. Our findings also suggest that higher grant expenditure on dwellings with poor pre-works energy efficiency rating and on retrofits such as attic insulation and heating system upgrades may have the highest energy efficiency improvements per unit of expenditure. Within the constraints of limited budgets for retrofit grant supports, this research can inform the redesign of grant schemes to achieve the greatest aggregate improvements in residential building energy efficiency.
Keywords: Q38; Q41; Q48; H23; 330; Energy efficiency; energy retrofits; retrofit intensity; vulnerable households; Abandonments